Increased EHHADH Expression Predicting Poor Survival of Osteosarcoma by Integrating Weighted Gene Coexpression Network Analysis and Experimental Validation. (4th May 2021) - Cui, Juncheng; Yi, Guoliang; Li, Jinxin; Li, Yangtao; Qian, Dongyang
Abstract : Enoyl-CoA hydratase and 3-hydroxyacyl CoA dehydrogenase (EHHADH), a member of the 3-hydroxyacyl-CoA dehydrogenase family, were previously demonstrated to be involved in the tumorigenesis of various cancer types. This study is aimed at determining of the diagnostic and prognostic value of EHHADH in osteosarcoma (OS). The overexpression of EHHADH was found both in OS and also other sarcoma types, and according to the retrospective cohort study, the EHHADH level was related to the overall survival and disease-free survival of the OS patients. Furthermore, knockdown of EHHADH under the influence of EHHADH small interfering RNA significantly suppressed the proliferation ability of the tumor cells. Moreover, EHHADH overexpressed was found in human OS tissues. In summary, the progression of OS could be enhanced by EHHADH, which may be a potential diagnostic and prognostic biomarker for OS patients.